Development of numerical tool for hybrid manufacturing process for titanium sheet metal forming - ACHOURI Mohamed (MATEC Web of Conferences, 2020)
The use of titanium in the aerospace industry has grown considerably in recent years in conjunction with the development of composite aircraft. In this way, improving titanium forming has become an important issue for the industry, both for productivity objectives and the ability to deliver basic parts according to the needs imposed by aircraft delivery rates, as well as for cost objectives. Currently, hot forming of titanium parts can be achieved through two processes: Super-plastic forming (SPF) or Hot Forming (HF). The aeronautical industry wanted to develop an innovative process for the manufacture of titanium parts by coupling the HF and SPF processes in order to exploit the advantages of these two technologies. The development of a mixed HF / SPF process will thus not only improve the rates and allow better control of the quality of the formed parts (thickness homogeneity), but also, by allowing forming at lower temperatures, this hybrid process presents a large interest at the energy plan. The study was devoted to the development of a hybrid HF/SPF process, carried out at a common temperature, allowing the “pre-forming” of the part in HF mode and the “calibration” of the part in SPF mode, while respecting a global cycle time compatible with the objectives of the aerospace industry and guaranteeing the quality expected for the final complex part. Improving the performance of the final part requires a development of numerical simulation tool of the forming process. The available simulation tool (ABAQUS/ Standard) must be adapted to define the best simulation strategy according to the simulated parts; moreover, it remains imperative to determine the input data (material behavior laws of titanium alloys) adapted to the cases to be treated (strain rate and process temperature).